2022
DOI: 10.1128/aac.01581-21
|View full text |Cite
|
Sign up to set email alerts
|

A Photoactivable Natural Product with Broad Antiviral Activity against Enveloped Viruses, Including Highly Pathogenic Coronaviruses

Abstract: The SARS-CoV-2 outbreak has highlighted the need for broad-spectrum antivirals against coronaviruses (CoVs). Here, pheophorbide a (Pba) was identified as a highly active antiviral molecule against HCoV-229E after bioguided fractionation of plant extracts. The antiviral activity of Pba was subsequently shown for SARS-CoV-2 and MERS-CoV, and its mechanism of action was further assessed, showing that Pba is an inhibitor of coronavirus entry by directly targeting the viral particle. Interestingly, the antiviral ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
1
19
0
2
Order By: Relevance
“…In a natural product screening study pheophorbide a (a chlorophyll derivative) showed a light‐dependent antiviral activity on SARS‐CoV‐2 and inhibited virus‐cell fusion. A similar mechanism was shown for temoporfin; however, it exhibited only moderate antiviral activity (582). Note, temoporfin has also been suggested in a pre‐print as a potential blocker of SARS‐CoV‐2 E channel based on a docking study (583).…”
Section: Other Applicationssupporting
confidence: 63%
“…In a natural product screening study pheophorbide a (a chlorophyll derivative) showed a light‐dependent antiviral activity on SARS‐CoV‐2 and inhibited virus‐cell fusion. A similar mechanism was shown for temoporfin; however, it exhibited only moderate antiviral activity (582). Note, temoporfin has also been suggested in a pre‐print as a potential blocker of SARS‐CoV‐2 E channel based on a docking study (583).…”
Section: Other Applicationssupporting
confidence: 63%
“…As células tumorais crescem mais rápido e, portanto, absorvem mais substâncias do ambiente externo, o que pode ajudar a aumentar a concentração intracelular do Fs [67]. Em 1912, Meyer-Betz demonstrou que a (HpD), é um composto isolado da hemoglobina, era um Fs muito poderoso com propriedades de localização tumoral [71,72].…”
Section: Resultados E Discussõesunclassified
“…Em 1912, Meyer-Betz demonstrou que a (HpD), é um composto isolado da hemoglobina, era um Fs muito poderoso com propriedades de localização tumoral [71,72].…”
Section: Resultados E Discussõesunclassified